Concentration of Heavy Metals Pb, Cu and Zn in Gonggong Snail (Strombus Canarium) From Sungai Enam and Dompak Marine Waters of Bintan Island Riau Islands Province - Br Sitepu, Desi Natalia E; Amin, Bintal; ', Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in June 2015 by collecting samples from Sungai Enam and Dompak coastal waters of Bintan Island of Riau Islands Province. The study used a survey method. The samples were collected from the intertidal area. The results showed that Pb content was found to be highest in large size of snails in Sungai Enam (4.6143 μg/g), the highest Cu content was found in medium size of snails in Dompak waters (4.7103 μg/g), and the highest Zn metal content was recorded in medium size of snails in Dompak waters (20.6790 μg/g). The results of this study also showed that MPI values obtained from Sungai Enam waters were 5.273 and for Dompak waters was 6.122. PTWI derived from the waters of Sungai Enam for Pb was equal to 1.6984 mg/kg of body weight per week. Cu amounted to 0.2887 mg/kg of body weight per week, whilst Zn amounted to 0.1870 mg/kg of body weight per week. PTWI derived from Dompak waters for Pb was 1.7581 mg/kg of body weight per week, Cu amounted to 0.2626 mg/kg of body weight per week whilst Zn amounted to 0.1269 mg/kg of body weight per weekKey Words : Heavy metal, gonggong snail (Strombus canarium), Bintan Island